Associations between childhood maltreatment and oxidative nucleoside damage in affective disorders. Issue 1 (11th August 2022) - Eriksen, Johanne Kofod Damm; Coello, Klara; Stanislaus, Sharleny; Kjærstad, Hanne Lie; Sletved, Kimie Stefanie Ormstrup; McIntyre, Roger S.; Faurholt-Jepsen, Maria; Miskowiak, Kamilla K.; Poulsen, Henrik Enghusen; Kessing, Lars Vedel; Vinberg, Maj
Abstract: Background: Childhood maltreatment is an established risk factor for incident unipolar disorder and bipolar disorder. It is separately observed that affective disorders (AD) are also associated with higher nucleoside damage by oxidation. Childhood maltreatment may induce higher levels of nucleoside damage by oxidation and thus contribute to the development of AD; however, this relation is only sparsely investigated. Methods: In total, 860 participants (468 patients with AD, 151 unaffected first-degree relatives, and 241 healthy control persons) completed the Childhood Trauma Questionnaire (CTQ). The association between CTQ scores and markers of systemic DNA and RNA damage by oxidation as measured by urinary excretion of 8-oxo-7, 8-dihydro-2′-deoxyguanosine (8-oxodG) and 8-oxo-7, 8-dihydroguanosine (8-oxoGuo) levels, respectively, was investigated. Results: In multiple regression models adjusted for sex- and age, 8-oxodG and 8-oxoGuo levels were found to be higher in individuals who had experienced more childhood maltreatment. These associations persisted in models additionally adjusted for body mass index, alcohol, and current smoking status. Emotional abuse, sexual abuse, and emotional neglect were principally responsible for the foregoing associations. Conclusions: Our findings of an association between childhood maltreatment and oxidative stress markers suggest that childhood maltreatment overall, notably emotional abuse and emotional neglect, is associated with enhanced systemic damage to DNA and RNA in adulthood. Further, individuals with AD reported a higher prevalence of childhood maltreatment, which may induce higher levels of nucleoside damage by oxidation in adulthood, possibly leading to increased risk of developing AD. Longitudinal studies are needed to clarify this relationship further.